ANALISA PEMBELIAN BARANG UNDERPRICED SEBAGI BENTUK KESALAHAN DELIK PENADAHAN: TINJAUAN YURIDIS YURISPRUDENSI MAHKAMAH AGUNG NOMOR 2/YUR/PID/2018 - Salim, Vina Putri; Ningrum, Tsamara Probo; Pratama, Risma Cahya Yudita; Fadilah, Nur (Gorontalo Law Review, 2020)
The purpose of this article is to find out the application of Supreme Court Jurisprudence Number 2 / Yur / Pid / 2018 which provides legal rules related to underpriced purchases as the fulfillment of the element "should be suspected that it was obtained from criminal offenses" in the offense. This research is legal research with a statutory approach and conceptual approach. The research results obtained are the application of the new legal rules in the Supreme Court Jurisprudence Number 2 / Yur / Pid / 2018 to the element of negligence in the offense delimitation in Article 480 of the Criminal Code. are required by law and do not exercise caution as required by law which is an element of negligence. In the element of not making guesses as required by law, it is related to the inner attitude of society in general, wherein movable objects the authorities are considered as the owner and society, in general, cannot know the market price of each movable object. This is different from immovable objects, where the authorities are not always the owners, where ownership is generally based on certificates so that the general public can know the price of the immovable object. In its development, registered and unregistered objects were born, whereas, in registered objects, the general public could find out the price of these registered objects, because ownership of these registered objects could be known publicly. About not taking the precautions required by law, which must be seen whether there is a behavior of the defendant to take preventive measures related to the origin of the goods, where when the buyer/seller has taken precautionary measures, it can be said that the buyer/seller has done the duty to be careful so that it cannot be said that negligence has occurred.